Combining X-ray micro-CT and microscopy-based images of two lianas species to derive structural, mechanical and functional relationships - Claudine Karlen; Pascal Turberg; Alexandre Buttler; Océane Martin; Fritz Schweingruber; Anastasios P. Vassilopoulos (Plant Systematics and Evolution, 2024)
This paper presents a biomechanical study of stems of two liana species, Clematis vitalba and Vitis vinifera , investigates the mechanical performance of these two liana species and attempts to enhance the understanding of structure–function relationships. The investigation involved mechanical testing of whole plant stems, supplemented by X-ray micro-CT (X-ray computed tomography at micron voxel size) imaging and 2D microscopic images of stained cross sections of the plant stems, to derive structure–function relationships with potential for application in bioinspired composite materials. The micro-CT images were compared to the microscopic images of stained cross sections, in order to show benefits and potential drawbacks of the X-ray micro-CT method with respect to traditional methods. The high-resolution 3D imaging capacity of micro-CT is exploited to explain the structural functionality derived from the mechanical testing. A simple finite element model is developed based on the plant topology derived by the micro-CT images and proved accurate enough to model the plant’s mechanical behaviour and assess the influence of their structural differences. The two plants exhibit different to each other physical and mechanical properties (density, strength and stiffness) due to their common growth form. Anatomical cross-sectional observation and X-ray micro-CT provide complementary information. The first method allows the identification of the lignified parts, supposedly more resistant mechanically, of these structures, while the second one provides a full 3D model of the structure, admittedly less detailed but providing the spatial distribution of density contrasts supposed to be important in the mechanical properties of the plant. The proposed methodological approach opens new perspectives to better understand the mechanical behaviour of the complex structure of plants and to draw inspiration from it in structural engineering.